A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis. Issue 18 (17th September 2017) - Liu, Qing-Long; Chen, A-Hong; Tang, Jin-Ying; Ma, Yan-Lei; Jiang, Zhi-Hua; Liu, Yan-Ping; Chen, Guang-Ying; Fu, Yan-Hui; Xu, Wei
Abstract: A new indole alkaloid, 17- O -methyl-19-( Z )-naucline (1 ), together with seven known alkaloids (2 –8 ), were isolated from the stems and leaves of Nauclea officinalis . The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons their data with those reported in the literature. 17- O -methyl-19-( Z )-naucline (1 ) showed significant inhibitory activity on nitric oxide production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells in vitro with an IC50 value of 3.6 μM. Abstract :